CAMPUR KODE BAHASA INGGRIS DALAM TUTURAN BERBAHASA INDONESIA PADA PROGRAM PW BANGET RADIO ELRIA BUANA JAMBI - Ade Rahima; Repha Krisdianti (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2020)
This research is aimed at describing two things, 1) the forms of English code-mixing in the Indonesian utterance on the program PW Banget by Radio announcer Elria Buana Jambi, 2) the factors of code-mixing of English into Indonesian language by Radio announcer Elria Buana Jambi. This research is qualitative descriptive with content analysis technique. The data of this research was acquired from the broadcast record of Radio Elria Buana Jambi and interview with announcer of Radio Elria Buana Jambi. The result of this research are. 1) the forms of code-mixing in the form of word, phrase, and clause are as follows: there are 38 quotations in the form of word pieces; there are 15 quotations in the form phrase pieces;  there are 2 quotations in the form of clause pieces; and the most dominant of code-mixing code occured is word pieces. 2) The dominant factor which causes the code-mixing by announcer of Radio Elria Buana Jambi is  the identification of role which covers social and registral which is derived from three causes: a) the choice of language is adjusted with the condition of broadcasting program;  b) the lack of English language ability of the announcer; c)  the use of uncommon English language by the youth (unconventional).